Geothermics - Geothermics (Elsevier, 2026)
Geothermics is an international journal devoted to the research and development of geothermal energy. The International Board of Editors of Geothermics, which comprises specialists in the various aspects of geothermal resources, exploration and development, guarantees a balanced, comprehensive view of scientific and technological developments in this promising energy field.
FI 0.75
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Geoscience; Geociencia; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Energía geotérmica; Recursos geotérmicos; Geotermia